LEGAL REGULATION OF GROUNDWATER EXTRACTION PROCESSES TO MEET THE NEEDS OF MILITARY UNITS - Pasika, S.; Chomko, D.; Opanasenko, O.; Khomiakov, D.; Skyba, O.; Pasika, R.; Horbachuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article highlights the legal aspects of groundwater regulation to meet the needs of the Armed Forces of Ukraine. The general tendencies of groundwater extraction to meet the needs of military units as components of national security and defense of Ukraine are considered and revealed. Given the insufficient resource provision, inefficient environmental monitoring system and inefficient use of resources in the security and defense sector, the issue of legal regulation of groundwater extraction processes to meet the needs of the Armed Forces of Ukraine as components of national security and defense of Ukraine is quite relevant and in demand. Currently, the issue of providing water to remote military units of the Armed Forces of Ukraine that do not have the ability to connect to a centralized water supply system and are forced to use wells to meet water supply needs is relevant. Analyzing the state of legal regulation of groundwater extraction processes to meet the needs of the Armed Forces of Ukraine, we note that there are a number of issues that are not regulated by the legislation of Ukraine, there are regulations that contain conflict rules. Achieving a balance of social, environmental and economic interests of military units as components of national security and defense of Ukraine, related to rational and balanced water consumption and water use, is one of the priority areas in improving mechanisms for state regulation of water resources in Ukraine. The means of implementing this direction is the development and implementation of coordinated and interconnected legislative, regulatory, organizational, economic, environmental and technical projects and measures to improve the quality of water resources, their rational and environmentally safe use, balancing economic water needs with resources and environmental opportunities water resource potential.